Early Pliocene anuran fossils from Kanapoi, Kenya, and the first fossil record for the African burrowing frog Hemisus (Neobatrachia: Hemisotidae). Issue 140 (March 2020) - Delfino, Massimo
Abstract: Isolated amphibian bones from the early Pliocene of Kanapoi (West Turkana, Kenya) help to improve the scarce fossil record of the late Neogene and Quaternary amphibians from East Africa. All currently available 579 bones are referable exclusively to the Anura (frogs and toads). More than half of the remains (366) are identified as Hemisus cf. Hemisus marmoratus, an extant species that still inhabits Kenya, but apparently not the northwest of the country and the Turkana area in particular. The rest of the remains are identified simply as Anura indet. because of poor preservation or non congruence with the relatively few African extant taxa whose osteology is known in detail. The Hemisus material represents the first fossil record for Hemisotidae, an endemic African family of peculiar, head-first burrowing frogs, whose sister taxon relationships indicate a divergence from brevicipitids in the Late Cretaceous or early Paleocene. The ecological requirements of extant H. marmoratus suggest that the Kanapoi area surrounding the fluvial and deltaic settings, from where the fossil remains of vertebrates were buried, was likely a grassland or relatively dry, open low tree-shrub savanna.